Experimental study on change characteristics of fractional flow rate of each structural unit in thick oil reservoir of Daqing Oilfield - PEI Xiuling, LI Jiaqi, MA Xufei, ZHANG Aixiang, ZHANG Leilei, LU Xiangguo, HE Xin (Youqicang pingjia yu kaifa)
In order to improve the understanding of the fractional rate law of injection and production ends in each structural unit of intraformational heterogeneous reservoir, aiming at the multi section and multi rhythm characteristics of thick oil layer in Lamadian Oilfield, Daqing, a model of intraformational heterogeneous reservoir is constructed by the “separate injection and separate production” core, and the effects of permeability gradient and injection speed on the fractional rate change law of water flooding are studied by physical simulation experiment. The results show that when water flooding reaches 0.4 PV, there is an inflection point in the flow rate curve. At the injection end, before 0.4 PV the injected water mainly enters into the high permeability layer, and after 0.4 PV, the liquid absorption of the middle and low permeability layer increases. For the positive rhythm reservoir, with the increase of permeability gradient, the swept volume of medium low permeability layer decreases and the recovery factor decreases; With the increase of the average permeability, the swept volume of the low and medium permeability layer increases, and the water flooding recovery increases. For the compound rhythm reservoir, the positive and negative compound rhythm is greater than the negative compound rhythm. When the injection rate is 0.6 mL/min at the injection end of heterogeneous core, with the increase of number of pore volumes（PV）, the fractional flow rate of high permeability layer increases, while that of low permeability layer decreases. When the injection rate is 0.9 mL/min and 1.2 mL/min, with the increase of number of pore volumes（PV）, the fractional flow rate of high permeability layer increases first and then decreases, while that of low permeability layer decreases first and then increases. With the increase of injection rate, the recovery rate and its percentage in the total recovery rate of low and medium permeability layers increase gradually. The research results have a certain guiding significance for the understanding of the mechanism of the split ratio at both ends of the injection and production in the deep heterogeneous reservoir.